Different DOACs Control Inflammation in Cardiac Ischemia-Reperfusion Differently. Issue 4 (19th February 2021) - Gadi, Ihsan; Fatima, Sameen; Elwakiel, Ahmed; Nazir, Sumra; Mohanad Al-Dabet, Moh'd; Rana, Rajiv; Bock, Fabian; Manoharan, Jayakumar; Gupta, Dheerendra; Biemann, Ronald; Nieswandt, Bernhard; Braun-Dullaeus, Ruediger; et al.
Abstract : Rationale: While thrombin is the key protease in thrombus formation, other coagulation proteases, such as fXa (factor Xa) or aPC (activated protein C), independently modulate intracellular signaling via partially distinct receptors. Objectives: To study the differential effects of fXa or fIIa (factor IIa) inhibition on gene expression and inflammation in myocardial ischemia-reperfusion injury. Methods and Results: Mice were treated with a direct fIIa inhibitor (fIIai) or direct fXa inhibitor (fXai) at doses that induced comparable anticoagulant effects ex vivo and in vivo (tail-bleeding assay and FeCl3 -induced thrombosis). Myocardial ischemia-reperfusion injury was induced via left anterior descending ligation. We determined infarct size and in vivo aPC generation, analyzed gene expression by RNA sequencing, and performed immunoblotting and ELISA. The signaling-only 3K3A-aPC variant and inhibitory antibodies that blocked all or only the anticoagulant function of aPC were used to determine the role of aPC. Doses of fIIai and fXai that induced comparable anticoagulant effects resulted in a comparable reduction in infarct size. However, unbiased gene expression analyses revealed marked differences, including pathways related to sterile inflammation and inflammasome regulation. fXai but not fIIai inhibited sterile inflammation by reducing the expression of proinflammatory cytokines (IL [interleukin]-1β, IL-6, and TNFα [tumor necrosis factor alpha]), as well as NF-κB (nuclear factor kappa B) and inflammasome activation. This anti-inflammatory effect was associated with reduced myocardial fibrosis 28 days post–myocardial ischemia-reperfusion injury. Mechanistically, in vivo aPC generation was higher with fXai than with fIIai. Inhibition of the anticoagulant and signaling properties of aPC abolished the anti-inflammatory effect associated with fXai, while inhibiting only the anticoagulant function of aPC had no effect. Combining 3K3A-aPC with fIIai reduced the inflammatory response, mimicking the fXai-associated effect. Conclusions: We showed that specific inhibition of coagulation via direct oral anticoagulants had differential effects on gene expression and inflammation, despite comparable anticoagulant effects and infarct sizes. Targeting individual coagulation proteases induces specific cellular responses unrelated to their anticoagulant effect. Abstract : Supplemental Digital Content is available in the text.